Towards modeling of comprehensive assessment for licensing in higher education - Cherednichenko, Olga; Yanholenko, Olha; Liutenko, Iryna Victorivna; Pylypenko, A. (Технологический Центр, 2013)
In the modern society information technologies, services, quality become the determinative factors of success of any business. The questions of quality management are especially relevant in social sphere, since organization oriented on quality of its processes provides the improvement of people living standards. Information computer technologies (ICT) are the powerful tool for increasing the performance of decision-making processes. Formalization of management problems and adequate mathematical models provide ICT with techniques and methods of solving the application problems in different domains and improving business performance. Higher education is a unique social and economic environment. The quality of its functioning influences many processes of successive development of society.Therefore elaboration of ICT in higher education domain remains the challenging problem for specialists in computer sciences.
Keywords: information systems; research process; business; higher education establishments; information computer technologies